Effect of graded level of sugarcane press mud in ration on carcass characteristics of crossbred (Landrace × Desi) pigs - SAHU, S; PATEL, B H M; DUTT, T; VERMA, A K (The Indian Journal of Animal Sciences, 2014)
The present study determined the effect of graded levels of sugarcane press mud (SPM) in the diet on carcass traits of crossbred Landrace pigs. Crossbred (Landrace × desi) piglets (28) randomly divided into 4 treatment groups, viz. T0: Control diet without SPM inclusion, T1: concentrate with 5% SPM inclusion, T2: concentrate with 10% SPM inclusion, T3: concentrate with 15% SPM inclusion, maintaining 3 barrows: 4 females under each group were used in this experiment. Iso-caloric and iso-proteinic diets were formulated for weaner (10–20kg), grower (20–50kg) and finisher (50–80kg). After the end of finisher stage, 2 barrows: 2 females from each group were slaughtered for carcass traits. All the major carcass traits were found non-significant among the treatment groups, but dressing % marginally variable among the treatment groups. Back fat thickness followed a linear trend from control to graded level of SPM supplementation while loin eye area did not follow any particular trend. Carcass length (cm) was lowest in T0 and highest in T2. All the parameters were comparable among the treatment groups. Similarly, SPM did not influence any carcass traits including primal cuts (%) as-well as edible and in edible offals. Chemical composition of loin eye muscle did not show any variation among the treatment groups. It can be concluded that inclusion of SPM up to 15% in swine ration did not cause any adverse effect on carcass traits.